ANALYSIS OF PRESENTATION ABILITY OF PGMI IAIN LANGSA STUDENTS IN THE RESEARCH METHODOLOGY COURSE - Chery Julida Panjaitan; Jelita Jelita; Ade Paramitha Utari (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
Presentation skills are one of the important skills for PGMI students at IAIN Langsa, especially in the Research Methodology course. This study aims to analyze the presentation skills of students of the PGMI study program at the State Islamic Institute of Langsa in the Research Methodology course. This study uses a descriptive qualitative approach with a sample of 50 students in the 4th semester of the PGMI study program at IAIN Langsa. Data collected through observation, interviews, questionnaires to determine the factors that influence the presentation skills of PGMI students IAIN Langsa, as well as documentation of assessments from lecturers of research methodology courses. The results showed that in general, the presentation skills of PGMI IAIN Langsa students are in the low category and must be improved again. Factors causing presentation skills such as self-confidence, mastery of material, and communication skills as well as anxiety and fear of negative judgment are things that have a significant effect on low presentation skills. The conclusion of this study is the need to improve student presentation skills that can be done with efforts such as public speaking training to increase self-confidence, seeking opportunities to speak in any activity, preparing themselves and materials for presentations and improving material delivery skills with the use of visual aids media can improve their presentation skills and be ready to face academic and professional challenges in the future.Keywords: Presentation Skills, PGMI IAIN Langsa Students, Research Methodology